2020
DOI: 10.1111/iju.14224
|View full text |Cite
|
Sign up to set email alerts
|

Surgical details and renal function change after robot‐assisted partial nephrectomy

Abstract: Abbreviations & Acronyms BMI = body mass index CI = confidence interval CKD = chronic kidney disease CT = computed tomography DM = diabetes mellitus DTPA = diethylenetetramine pentaacetic acid GFR = glomerular filtration rate IQR = interquartile range PN = partial nephrectomy RAPN = robot-assisted partial nephrectomy WIT = warm ischemic time Objectives: To investigate whether differences in surgical details during robot-assisted partial nephrectomy impact postoperative renal function. Methods: Patient, tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In recent years, robotic surgery has been rapidly accepted for a wide variety of surgical procedures due to its definite benefits, including three‐dimensional (3D) clear vision, suppression of physiological tremor and fine manipulations of forceps with a wide range of motion 3 . In the field of kidney surgery as well, utilization of robot‐assisted PN (RAPN) has markedly increased as the standard of care for clinical T1 tumors 4–6 . Furthermore, since the initial report by Klinger et al, 7 RARN has been considered a promising alternative to ORN or LRN, and the proportion of RCC patients undergoing RARN has significantly increased over the past decade 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, robotic surgery has been rapidly accepted for a wide variety of surgical procedures due to its definite benefits, including three‐dimensional (3D) clear vision, suppression of physiological tremor and fine manipulations of forceps with a wide range of motion 3 . In the field of kidney surgery as well, utilization of robot‐assisted PN (RAPN) has markedly increased as the standard of care for clinical T1 tumors 4–6 . Furthermore, since the initial report by Klinger et al, 7 RARN has been considered a promising alternative to ORN or LRN, and the proportion of RCC patients undergoing RARN has significantly increased over the past decade 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Renorrhaphy might damage intraparenchymal vessels and compress the renal parenchyma, which would lead to further devascularization of normal nephrons. 6 Our GasLESS PN also excluded renorrhaphy in principle, which may have contributed to further improvement in renal function preservation by avoiding this possible negative impact. In the present study, renorrhaphy was performed in 16 patients (4%) based on the intraoperative findings.…”
Section: Discussionmentioning
confidence: 93%
“…Renorrhaphy is another classic procedure to ensure hemostasis after tumor removal, and most surgeons consider renorrhaphy to be an essential step for PN. Nevertheless, it has been reported that suturing the renal bed might negatively affect postoperative renal function by devascularizing the normal renal parenchyma 6 . Previous studies also suggested that renorrhaphy may increase the risk of pseudoaneurysm by lacerating arterioles 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another meta-analysis showed no significant difference in the incidence of postoperative complications between SILR and DLR [28]. Hemostatic running sutures frequently performed during RAPN, especially deep in the renal medulla, may encircle the branches of vessels traveling in proximity [29]. Therefore, SILR is thought to significantly reduce the incidence of pseudoaneurysms as suturing the renal parenchyma during renorrhaphy helps prevent injury to the renal vessels [28].…”
Section: Discussionmentioning
confidence: 99%